1982
DOI: 10.1104/pp.69.2.385
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ethylene Biosynthesis by Aminoethoxyvinylglycine and by Polyamines Shunts Label from 3,4-[14C]Methionine into Spermidine in Aged Orange Peel Discs

Abstract: The flux of radioactivity from 3,4-114Clmethionine into S-adenosyl_L-methionine (SAM), 1-aminocyclopropane-l-carboxylic acid (ACC), sperm- (11), and by wounded tissue of citrus fruit (12, 29) has been previously reported. The induction of ethylene formation by ABA and the inhibitory effect of AVG on its production in citrus bud culture and leaf explants were also studied (10, 21). In the present investigation, we have used orange peel tissue to study relative incorporation of radioactivity from 3,4-[14CJmethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
69
2
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(76 citation statements)
references
References 17 publications
4
69
2
1
Order By: Relevance
“…2-4) which was maintained for each successive whorl of adventitious roots that emerged from the stem base for the duration of the starvation treatment (up to 24 d). Our results may seem to be at variance with those of others (6,14) who found that it was the presence of phosphate that inhibited ethylene biosynthesis in a wide range of higher plant tissues, including carrot root and etiolated stem segments of pea (Pisum sativum) and tomato (Lycopersicon esculentum). Inhibition of ethylene production by phosphate also takes place in fruit tissues (6,14) where it acts on the conversion of ACC to ethylene (14).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…2-4) which was maintained for each successive whorl of adventitious roots that emerged from the stem base for the duration of the starvation treatment (up to 24 d). Our results may seem to be at variance with those of others (6,14) who found that it was the presence of phosphate that inhibited ethylene biosynthesis in a wide range of higher plant tissues, including carrot root and etiolated stem segments of pea (Pisum sativum) and tomato (Lycopersicon esculentum). Inhibition of ethylene production by phosphate also takes place in fruit tissues (6,14) where it acts on the conversion of ACC to ethylene (14).…”
Section: Discussioncontrasting
confidence: 57%
“…Our results may seem to be at variance with those of others (6,14) who found that it was the presence of phosphate that inhibited ethylene biosynthesis in a wide range of higher plant tissues, including carrot root and etiolated stem segments of pea (Pisum sativum) and tomato (Lycopersicon esculentum). Inhibition of ethylene production by phosphate also takes place in fruit tissues (6,14) where it acts on the conversion of ACC to ethylene (14). However, the concentrations of phosphate that were used were high (50-100 mM), greatly in excess of those that plant roots would encounter under physiological conditions; commonly, hydro- (Fig.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…According to Apelbaum et al (4) and Suttle (27), PAs inhibit ethylene biosynthesis primarily by inhibiting ACC conversion to ethylene. Other investigators found evidence for an inhibition at the conversion of SAM to ACC (8).…”
mentioning
confidence: 98%